Finite nonabelian p-groups all of whose subgroups are q-self dual - Janko, Zvonimir (Journal of algebra and its applications, 2014)
A finite p-group G is q-self dual if every quotient of G is isomorphic to a subgroup of G. Here, we determine finite 2-groups G all of whose subgroups are q-self dual (Theorem 3) and in case p > 2 we get a classification of such groups only under the additional assumptions that Ω1(G) is abelian (Theorem 4).
Published online: 27 December 2013
Gesehen am 23.02.2018